Estimating the Effects of Length of Exposure to Instruction in a Training Program: The Case of Job Corps - Flores, Carlos A.; Flores-Lagunes, Alfonso; Gonzalez, Arturo; Neumann, Todd C. (The Review of Economics and Statistics, 2012)
We semiparametrically estimate average causal effects of different lengths of exposure to academic and vocational instruction in the Job Corps (JC) under the assumption that selection into different lengths is based on a rich set of observed covariates and time-invariant factors. We find that the estimated effects on future earnings increase in the length of exposure and that the marginal effects of additional instruction decrease with length of exposure. We also document differences in the estimated effects across demographic groups, which are particularly large between males and females. Finally, our results suggest an important lock-in effect in JC training. No rights reserved. This work was authored as part of the Contributor's official duties as an Employee of the United States Government and is therefore a work of the United States Government. In accordance with 17 U.S.C. 105, no copyright protection is available for such works under U.S. law..